Peripheral and central macrophages in obesity - Mukherjee, Sayani; Skrede, Silje; Haugstøyl, Martha; López, Miguel; Fernø, Johan (Frontiers in Endocrinology, 2023)
Obesity is associated with chronic, low-grade inflammation. Excessive nutrient intake causes adipose tissue expansion, which may in turn cause cellular stress that triggers infiltration of pro-inflammatory immune cells from the circulation as well as activation of cells that are residing in the adipose tissue. In particular, the adipose tissue macrophages (ATMs) are important in the pathogenesis of obesity. A pro-inflammatory activation is also found in other organs which are important for energy metabolism, such as the liver, muscle and the pancreas, which may stimulate the development of obesity-related co-morbidities, including insulin resistance, type 2 diabetes (T2D), cardiovascular disease (CVD) and non-alcoholic fatty liver disease (NAFLD). Interestingly, it is now clear that obesity-induced pro-inflammatory signaling also occurs in the central nervous system (CNS), and that pro-inflammatory activation of immune cells in the brain may be involved in appetite dysregulation and metabolic disturbances in obesity. More recently, it has become evident that microglia, the resident macrophages of the CNS that drive neuroinflammation, may also be activated in obesity and can be relevant for regulation of hypothalamic feeding circuits. In this review, we focus on the action of peripheral and central macrophages and their potential roles in metabolic disease, and how macrophages interact with other immune cells to promote inflammation during obesity.